Correction: A statistical simulation model to guide the choices of analytical methods in arrayed CRISPR screen experiments. - Chang Sik Kim; Jonathan Cairns; Valentina Quarantotti; Bogumil Kaczkowski; Yinhai Wang; Peter Konings; Xiang Zhang (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0307445.].